On “Inequality Traps” and Development Policy - Rao, Vijayendra (World Bank, Washington, DC, 2012)
There are inequalities in the world, among individuals and among groups that get reproduced across generations. In the World Development Report 2006 these are referred to as inequality traps. Inequality traps are similar to poverty traps in that they serve to keep people poor and destitute. But equality traps differ from poverty traps in that they refer to a reinforcing system of economic, political and social structures that lead to what social scientists have called durable inequality.